The Influence of Urbanization, Population Density, and Poverty Rate on Crime in the City of Bandung - Maulani, Dwi Cahya; Purwaningsih, Vitriyani Tri; Aida, Neli (Jurnal Ekonomi Pembangunan, 2024)
This study analyzes the influence of population density, poverty, and urbanization on the crime rate in the city of Bandung using a multiple linear regression method with time series data for the 2017-2022 period sourced from BPS and related agencies. The results of the study show that population density and poverty have a significant influence on crime, where population density creates social pressure and conflict, while poverty encourages crime as a form of economic survival. In contrast, urbanization has no significant effect on crime, which is thought to be due to the equitable distribution of urbanization or the effectiveness of its impact management policies. This research emphasizes the importance of poverty alleviation and spatial management in reducing crime rates in the city of Bandung.